Peculiarities of ophthalmohemodynamics in patients with severe eye trauma complicated by ciliochoroid detachment (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Posttraumatic ciliochoroid detachment (CCD) is one of the most serious complications of eye injury which can lead to blindness, and even to subatrophy of the eyeball. The study of the pathogenesis of this type of eye injury is of great importance for the development of pathogenetically directed method of treatment of patients with eye injury complicated by CCD. The investigation of hemodynamic disorders in patients with eye injury complicated by CCO as one of the parts of pathogenesis of CCD formation is in individual works of domestic and foreign ophthalmologists. Therefore, this issue remains insufficiently understood and requires further development. Objective: To study the characteristics of ophtalmohemodynamics in patients with severe eye injury complicated by CCD. Material and methods. Clinical studies were conducted in 98 patients with severe eye injury: 12 patients with severe trauma of the eyeball complicated by CCD, 86 patients with contusion eye without CCD. Patients underwent a comprehensive eye examination, ultrasound diagnostics of the position of the ciliary body and the height of its detachment with the help of short high-frequency probes 20 and 50 MHz. Hemodynamic study of healthy and sick eye was performed by the standard method by rheographic computer complex Reokom (Kharkiv, Ukraine). Results. Ophthalmohemodynamic study in patients with severe eye injury, aggravated by ciliochorioid detachment showed significant impairment of blood supply both the injured and the paired eye in all groups of patients. For example, RQ of the injured eye was (1.1 ± 0.1) %, of the paired eye — (2.8 ± 0.4) % the norm being RQ (3.2 ± 0.1 %) for this age group. There were not found reliable differences of RQ in patient with eye contusion (0.97 ± 0.27) % and a penetrating wound (1.24 ± 0.53) %. There were revealed significant hemodynamic disturbances in the eyes with severe trauma complicated by CCD in all periods after the injury, but the tendency to shortage of blood supply is more marked in the early posttraumatic period — up to 15 days after injury. Significant hemodynamic disturbances are observed in any CCD length, but in the length of CCD on all circumference were most pronounced (RQ = 0.97 ± 0.17 % o) as compared to 1.17 ± 0.22 (% o.) Conclusion. Severe eye injury, complicated with CCD, regardless the nature of the injury, is associated with significant hemodynamic disturbances, manifested by decreased rheographic factor in the injured eye by 74 % compared with the age norm and by 69 % in comparison with the paired eye. Availability of cyclodialysis further aggravates hemodynamic disorders (39.5 %) in severe eye injury complicated by CCD. Disturbed blood supply of the eye in severe eye injury, aggravated by CCD was observed in different periods after the injury, but in the first 15 days these disturbances were most pronounced. However, in the later periods after the injury hemodynamic instability remains significant. In this regard, there is necessity for a specific treatment is not only in the early but also in the late periods after injury.
Keywords: Severe eye trauma; ciliochoroid; ophthalmohemodynamics